The role of cell membrane-coated nanoparticles as a novel treatment approach in glioblastoma - Allami, Pantea; Heidari, Arash; Rezaei, Nima (Frontiers in Molecular Biosciences, 2023)
Glioblastoma multiform (GBM) is the most prevalent and deadliest primary brain malignancy in adults, whose median survival rate does not exceed 15 months after diagnosis. The conventional treatment of GBM, including maximal safe surgery followed by chemotherapy and radiotherapy, usually cannot lead to notable improvements in the disease prognosis and the tumor always recurs. Many GBM characteristics make its treatment challenging. The most important ones are the impermeability of the blood-brain barrier (BBB), preventing chemotherapeutic drugs from reaching in adequate amounts to the tumor site, intratumoral heterogeneity, and roles of glioblastoma stem cells (GSCs). To overcome these barriers, the recently-developed drug-carrying approach using nanoparticles (NPs) may play a significant role. NPs are tiny particles, usually less than 100 nm showing various diagnostic and therapeutic medical applications. In this regard, cell membrane (CM)-coated NPs demonstrated several promising effects in GBM in pre-clinical studies. They benefit from fewer adverse effects due to their specific targeting of tumor cells, biocompatibility because of their CM surfaces, prolonged half-life, easy penetrating of the BBB, and escaping from the immune reaction, making them an attractive option for GBM treatment. To date, CM-coated NPs have been applied to enhance the effectiveness of major therapeutic approaches in GBM treatment, including chemotherapy, immunotherapy, gene therapy, and photo-based therapies. Despite the promising results in pre-clinical studies regarding the effectiveness of CM-coated NPs in GBM, significant barriers like high expenses, complex preparation processes, and unknown long-term effects still hinder its mass production for the clinic. In this regard, the current study aims to provide an overview of different characteristics of CM-coated NPs and comprehensively investigate their application as a novel treatment approach in GBM.